A Study on Social Health and its Effective Factors - fatemeh modiri; khadijeh safiri; fatemeh mansourian (توسعه اجتماعی)
Social health as a factor to assess and cognitive their social function is influenced by several factors that these factors in surveys, have been introduced varied، fragmented and sometimes contradictory and it needed a comp, rehensive review of these factors and we will bring to this matter in this article. This study is a documental and use of 22 scientific article and thesis, and examined this issue meta-analysis method using the software comprehensive Meta analysis and thereby indicate which of the factors and to what degree are accepted. Findings of descriptive and quantitative composition of the research results show: most of the people (56.3%) have moderate level of social health. Communication skills, quality of life, leisure activities, age, socioeconomic status and gender according to the size effect and significant level are affected on social health, but marital status, education and social health aren’t reasonable and significant relations. Findings confirm theories of Keyes, Smith, Frans and Matson.